Keunggulan Kompetitif Yogya Mall Tegal yang dipengaruhi Persepsi Digital Marketing, Reputasi Harga, dan Kualitas Produk - Yuniarti Herwinarni; Sari Wiyanti; Faiz Irsyad Prasetyo (Journal of Innovative and Creativity, 2025)
Mall business competition in Tegal is very high, the location is close to each other and each has a competitive advantage. Yogya Mall Tegal is currently not only competing with malls in Tegal but competing with online stores whose products are unique and diverse, competitive prices and respond to all needs. Perceptual factors of digital marketing, price reputation and product quality can increase the competitive advantage of Yogya Mall Tegal. The purpose of this study was to analyze the decline of Yogya Mall Tegal's competitive advantage and the factors that influence it. This research method uses qualitative and quantitative research approaches. The sample in this study amounted to 100 respondents, with the sampling technique is non probability sampling through accidental sampling method. The data used is primary data which will be processed using SPSS 25. The results of this study obtained the results of the t test results obtained tcount> ttable (1.965> 1.661) with a sig value. 0.015 <0.05 means H1 is accepted. The t test results obtained tcount> ttable (2.091> 1.661) with a sig value. 0.039 <0.05 means H2 is accepted. The t test results obtained tcount> ttable (1.913> 1.661) with a sig value. 0.049 <0.05 means H3 is accepted. From the results of the F test obtained Fcount> Ftable (11.75> 2.696) and a significance value of 0.000 <0.05 means H4 is accepted The results of this study prove that the three variables, namely Perception of Digital Marketing, Price Reputation and Product Quality are factors that support the formation of Yogya Mall Tegal Competitive Advantage.